Terror in France: The Rise of Jihad in the West by Gilles Kepel (Princeton: Princeton University Press, 2017. 240 pages.) (American Journal of Islam and Society, 2017)
Gilles Kepel is a French political scientist and Arabist with a global reputationfor understanding Islam as an ideological, political, and social force.Among his books are Muslim Extremism in Egypt: The Prophet andPharaoh (1985), Allah in the West: Islamic Movements in America and Europe(1996), Jihad: The Trial of Political Islam (2003), The Roots of RadicalIslam (2005), Al Qaeda in Its Own Words (2006; co-edited with Jean-PereerMilelli), The War for Muslim Minds: Islam and the West (2006), and BeyondTerror and Martyrdom: The Future of the Middle East (2010). In Terror in France: The Rise of Jihad in the West, his latest and bestsellingbook for 2016, he makes the case that this phenomenon has passedthrough two phases and recently entered a third one. The first phase began inthe 1990s with Mohamed Kelkal and was related to the Algerian civil war.Terrorism was used as a tool to force France to end its support for the coupthat had negated the Islamists’ electoral victory. The second phase began in2012 with the Toulouse and Montauban shootings that were linked to al-Qaeda. Globalization now enabled a network of jihadists linked to Afghanistanto serve the Muslim cause. The (posited) third phase, which would developafter the Arab Spring was launched, would see French jihadists sent to fight ...